Selection of F6 soybean population for pod shattering resistance - Ayda Krisnawati; ANDY SOEGIANTO; BUDI WALUYO; KUSWANTO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Krisnawati A, Soegianto A, Waluyo B, Kuswanto. 2019. Selection of F6 soybean population for pod shattering resistance. Biodiversitas 20: 3340-3346. Pod shattering is one of the major soybean constraints in Indonesia. This research aimed to evaluate the resistance of soybean F6 population to pod shattering and characterize the selected lines for their agronomic performances. The materials used were 147 F6 lines derived from six crossing combinations. The check varieties consisted of Dega 1, Detap 1, and Anjasmoro. The experiment was arranged in a randomized block design with two replications. At R8 stage, thirty pods were randomly detached from five sample plants of each line to be used for evaluation of pod shattering resistance using an oven-dry method. The variability of pod shattering was showed after the treatment of 60°C oven temperature. The shattering resistance of 147 F6 lines was classified into 52 highly resistant, 49 resistant, two moderately resistant, ten susceptible, and 34 highly susceptible lines. The pod-shattering resistant lines could be used for further improvement in the breeding program. Anjasmoro variety was effective to be used as gene source for shattering resistant. Simultaneous selection based on yield (30% selection intensity) and shattering resistance selected six lines which have early maturity and large seed size, hence they could be further evaluated in several locations in the next breeding stage.